Programmed cell death in aging - Tower, John (Ageing research reviews, 2015)
•Programmed cell death (PCD) pathways are implicated in aging and aging-related disease.•Increased PCD during mammalian aging is implicated in tissue atrophy and neurodegenerative disease.•Cancer cells and senescent cells are resistant to PCD.•Fungal life span is limited by PCD pathways. Programmed cell death (PCD) pathways, including apoptosis and regulated necrosis, are required for normal cell turnover and tissue homeostasis. Mis-regulation of PCD is increasingly implicated in aging and aging-related disease. During aging the cell turnover rate declines for several highly-mitotic tissues. Aging-associated disruptions in systemic and inter-cell signaling combined with cell-autonomous damage and mitochondrial malfunction result in increased PCD in some cell types, and decreased PCD in other cell types. Increased PCD during aging is implicated in immune system decline, skeletal muscle wasting (sarcopenia), loss of cells in the heart, and neurodegenerative disease. In contrast, cancer cells and senescent cells are resistant to PCD, enabling them to increase in abundance during aging. PCD pathways limit life span in fungi, but whether PCD pathways normally limit adult metazoan life span is not yet clear. PCD is regulated by a balance of negative and positive factors, including the mitochondria, which are particularly subject to aging-associated malfunction.